2007
DOI: 10.1126/science.1133680
|View full text |Cite
|
Sign up to set email alerts
|

Strong Relationship Between DMS and the Solar Radiation Dose over the Global Surface Ocean

Abstract: Marine biogenic dimethylsulfide (DMS) is the main natural source of tropospheric sulfur, which may play a key role in cloud formation and albedo over the remote ocean. Through a global data analysis, we found that DMS concentrations are highly positively correlated with the solar radiation dose in the upper mixed layer of the open ocean, irrespective of latitude, plankton biomass, or temperature. This is a necessary condition for the feasibility of a negative feedback in which light-attenuating DMS emissions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
273
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(303 citation statements)
references
References 24 publications
16
273
4
Order By: Relevance
“…Vallina and Simó [39] have indicated a strong correlation between DMS concentrations in the upper ocean and the solar radiation dose, which supports one of the tenets of the CLAW hypothesis, namely that increased solar radiation will enhance the DMS flux. However, whether this enhanced DMS flux results in a negative feedback via an impact on the cloud albedo remains an open question.…”
Section: Discussionsupporting
confidence: 52%
“…Vallina and Simó [39] have indicated a strong correlation between DMS concentrations in the upper ocean and the solar radiation dose, which supports one of the tenets of the CLAW hypothesis, namely that increased solar radiation will enhance the DMS flux. However, whether this enhanced DMS flux results in a negative feedback via an impact on the cloud albedo remains an open question.…”
Section: Discussionsupporting
confidence: 52%
“…0.15uC or kg m 23 from the surface reference value (2 m depth). For each radiation band, subsurface irradiance, vertically integrated irradiance in the mixed layer (Vallina and Simó 2007), and that at the bottom of the mixed layer were computed for the duration of each experiment (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…At the global scale, this seems to translate into a strong correlation between average irradiance in the upper mixed layer and DMS concentrations (Vallina and Simó 2007;Lana et al 2012). Algal DMSP synthesis has been interpreted as a physiological adaptation to high light and nutrient limitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of a global DMS database as well as local DMS time series (BATS in the Sargasso Sea and Blanes Blay in the NW Mediterranean) have revealed that the solar radiation dose in the upper mixed layer (or SRD) is the climatic factor that seems to drive DMS dynamics. [2][3][4] maximum in surface waters, even in regions where a phytoplankton biomass proxy like chlorophyll-a (CHL) shows an annual minimum in summer [5][6][7] (subtropical and low temperate regions), a feature known as the DMS summer-paradox. [8] The SRD is highly related to the ultraviolet radiation (UVR) dose in the upper mixed layer of the ocean.…”
Section: What Is the Climatic Factor That Drives Oceanic Dms Productimentioning
confidence: 99%